Association between polycystic ovary syndrome and venous thromboembolism: A systematic review and meta-analysis. Issue 185 (January 2020) - Gariani, Karim; Hugon-Rodin, Justine; Philippe, Jacques; Righini, Marc; Blondon, Marc
Abstract: Aims: Polycystic ovary syndrome (PCOS) is very prevalent and commonly treated with prothrombotic combined oral contraceptives (COC). Our aim was to systematically review the available evidence to evaluate the risk of venous thromboembolism (VTE) associated with PCOS, and whether observed increased risks may be explained by a higher prevalence of obesity and hormonal treatments. Method: For this systematic review and meta-analysis, two authors independently searched MEDLINE, EMBASE and conference proceedings (ISTH, WHITH) from inception through 4.2019 for studies reporting the association of PCOS with VTE risk. Study quality was assessed and relative risk estimates were pooled through random effect models. Results: We identified 5 large observational studies published between 2004 and 2018, most commonly using administrative data, set in Denmark, the USA or the United Kingdom. Compared with participants without PCOS, participants with PCOS had greater risks of VTE in unadjusted analyses (pooled OR 1.70, 95%CI 1.42–2.04, I 2 67%). In three studies reporting analyses adjusted for at least obesity and hormonal treatments, PCOS was still associated with greater risks of VTE (pooled OR 1.89, 95%CI 1.60–2.24, I 2 27%). Conclusions: PCOS appears to be a risk factor for VTE, independently of its associated excess weight and greater use of combined oral contraceptives. This should be taken into account in the pharmacological management of PCOS. Highlights: We investigated the association between polycystic ovary syndrome (PCOS) and venous thromboembolism (VTE). A comprehensive search identified 5 observational studies which were included in a meta-analysis. Participants with PCOS had greater risks of VTE, also after adjustment for excess weight and use of contraceptives. This apparent risk should be taken into account in the pharmacological management of PCOS.